Thermal Comfort and Air Change Rate Study for a Naturally Ventilated Classroom: A Case Study of El-baida City, Libya - Sulaiman M . Boghandora, Tarek A. Hamad (Journal of Pure & Applied Sciences, 2020)
Nowadays in building and environment, it is of a functional requirement to fulfill a robust design by diminishing the energy consumption while keeping the environmental factors surrounding the individuals within a comfort range. Natural ventilation in buildings is considered as an advantageous attempt serving those purposes. In Libya, most of the educational buildings are utilizing the natural ventilation systems where the energy consumption is minimized while the internal temperatures and humidity are constrained, indoor air is replenished and all other contaminants are reduced. Although extensive oversea researches have been carried out in this regard, few studies have touched the thermal comfort and internal environmental attributes influencing the performance of students in Libya. The main objective of this study was to investigate qualitatively and quantitatively the thermal comfort and air change rate of a naturally ventilated classroom located in El-baida City-Libya. The thermal comfort of one classroom, was evaluated by calculating the values of the Predicted Mean Vote (PMV) and Predicted Percentage Dissatisfied (PPD) indices. This was accomplished by measuring the six main indoor parameters of the thermal comfort, namely were, air temperature, Mean Radiant Temperature (MRT), relative humidity, air velocity, activity level and clothing insulation. Also, (PMV) and (PPD), were calculated in parallel to ASHRAE 55-2010 and ISO 7730 by using MATLAB. Additionally, a field survey was completed by distributing comfort questionnaires to estimate Thermal Sensation Votes (TSV), which were then compared with computed (PMV) and (PPD). The results highlighted that while computed values of (PMV) and (PPD) for the classroom, were thermally satisfactory according to ASHRAE standard 55 and ISO 7730, the Thermal Sensation Vote (TSV) based on the questionnaire, showed that the classroom did not satisfy the thermal criteria in ASHRAE.